Selective Serotonin Reuptake Inhibitor Fluoxetine Inhibits Replication of Human Enteroviruses B and D by Targeting Viral Protein 2C - Ulferts, Rachel (American Society for Microbiology, 2013)
Although the genus Enterovirus contains many important human pathogens, there is no licensed drug for either the treatment or the prophylaxis of enterovirus infections. We report that fluoxetine (Prozac)—a selective serotonin reuptake inhibitor—inhibits the replication of human enterovirus B (HEV-B) and HEV-D but does not affect the replication of HEV-A and HEV-C or human rhinovirus A or B. We show that fluoxetine interferes with viral RNA replication, and we identified viral protein 2C as the target of this compound.